Contemporary and social wisdom in Azhar Kamal's Poetry - Dr. Rahmat Ali Shad; Dr.Farzana Riaz (Zaban-o-Adab, 2023)
Azhar Kamal has created various known genera of poetry like Hamad, Naat, Manqabat, Ghazal and Nazam. Out of many dimensions of his personality as a poet, the most important aspect is that he is a poet of modern trends and bright possibilities of human life. He is well aware of modern literary trends and thoughts in present-day poetry. His poetry reveals the current situations along with bitter realities of life found in our society. He has not only coined new words but also has invented novel ways of expression according to his poetic needs. Maturity of thought, variety of subject, social conciousness, familiarity with modern trends and fine blend of classical and modern-day trends in verse are important chracteristics of his poetry. Through all these features he has attempted wonderfully to impart new ideas to Urdu literature.